Disparity In Judges' Determinations Regarding The Confirmation Of Marriage For Underage Sirri Marriages From The Perspective Of Legal Certainty - Lailatul Khomariyah; Musthafa Syukur (International Journal of Science and Environment (IJSE), 2025)
This study aims to understand and analyze disparities in judges' decisions on marriage validation for secret marriages conducted by underage couples and the legal implications (consequences) that arise. The type of method used in this study is a normative legal research method, using a statutory approach. The findings of this study indicate that the judge rejected the marriage validation case in Decision No. 951/Pdt.P/2023/PA.Krs and Decision No. 59/Pdt.P/2019/PA. Apn reviewed the legal certainty aspect in accordance with the applicable laws and referred to the fatwa of the Secretary of the Supreme Court of the Republic of Indonesia No. 231/PAN/HK. 05/01/2019, which states that marriages involving minors who do not meet the minimum age requirement for marriage must be renewed through tajdid nikah and registered. This relates to the judge's decision to grant the marriage validation case in Judgment No. 614/Pdt.P/2022/PA.Tg and No. 58/Pdt.P/2023/PA. Rtg reviews the aspect of maslahah mursalah (public interest) within the family. This study aims to provide recommendations to enhance consistency and fairness in the enforcement of laws related to underage secret marriages, particularly for unregistered marriages, and to promote public awareness of the importance of marriage registration to ensure their legal rights.